2014
DOI: 10.1055/s-0034-1372640
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Stride Angle and Strike Pattern on Running Economy

Abstract: This study aimed to investigate the relationship between stride angle and running economy (RE) in athletes with different foot strike patterns. 30 male runners completed 4 min running stages on a treadmill at different velocities. During the test, biomechanical variables such as stride angle, swing time, contact time, stride length and frequency were recorded using an optical measurement system. Their foot strike pattern was determined, and VO2 at velocities below the lactate threshold were measured to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
(24 reference statements)
3
25
0
1
Order By: Relevance
“…The sagittal plane ankle angle can be interpreted as an index of foot strike pattern, where greater than 10 degrees indicates a highly likely heel strike [32]. Although our findings are in agreement with previous research reporting no differences in COT between differing strike patterns when habitual forefoot and rearfoot strikers also run in their non-preferred strike pattern [9], other studies have suggested that habitual rearfoot strikers [17,20] or even habitual forefoot strikers [24] are more economical. This study found improved COT without significant changes in sagittal plane ankle angle and no association between the changes in these variables.…”
supporting
confidence: 91%
“…The sagittal plane ankle angle can be interpreted as an index of foot strike pattern, where greater than 10 degrees indicates a highly likely heel strike [32]. Although our findings are in agreement with previous research reporting no differences in COT between differing strike patterns when habitual forefoot and rearfoot strikers also run in their non-preferred strike pattern [9], other studies have suggested that habitual rearfoot strikers [17,20] or even habitual forefoot strikers [24] are more economical. This study found improved COT without significant changes in sagittal plane ankle angle and no association between the changes in these variables.…”
supporting
confidence: 91%
“…It has been demonstrated that runners with shorter GCT were not only faster but also more energy efficient than runners with longer GCT (27,34). Kong and colleagues (23) argued that shorter GCT might be related to good running economy because there is less time for the braking force to decelerate forward motion of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the relationship between RE and technique have typically been small cohort studies ( n < 25 [45,47]) of relatively homogeneous groups of runners (37,38,45), limited kinematic measurements and methods (e.g., stride parameters [16,37,38]), or measurements of RE and kinematics at different speeds or under different conditions (34,47). Consequently, the overall relationship between specific kinematic variables and RE and performance remains opaque, such that a recent review of strategies to improve RE provided no recommendations with regard to running technique (5).…”
mentioning
confidence: 99%
“…The configuration of the lower limb at touchdown might also be expected to be a critical aspect of running technique (8). This includes the relatively simplistic classification of footstrike type (16,37), which can be more precisely measured as foot angle at touchdown, as well as the angles of the shank and thigh. Since RE has been suggested to relate to the stiffness of the stance leg (15), and motion of the swinging leg may contribute ~20% to the cost of locomotion (30), the minimum knee joint angles during stance and swing phases might also be key variables.…”
mentioning
confidence: 99%